Methods of protein extraction from house crickets (Acheta domesticus) for food purposes - Cunha, Nair (2025)
Global population is projected to reach 9.1 billion by 2050, emphasizing the need for increased food production. Edible insects, such as house crickets (Acheta domesticus), emerged as promising due to higher nutritional value and efficient feed conversion rates compared to conventional protein sources. Incorporating insect powders into new food products can improve consumer acceptance but often leads to poor technological food processing functionality and/or undesirable organoleptic characteristics. Protein isolates have proven to be effective in enhancing this functionality and consumer acceptance, but existent protein extraction methods still lack improvements concerning the optimization of protein extraction rates. This study aimed to address this gap by developing and comparing the yield of three different protein extraction methods using sodium hydroxide, ascorbic acid or alcalase from house crickets (Acheta domesticus) for food applications. Protein extraction was performed on cricket powder with a mean protein content of 46.35 g/100 g, and the results were evaluated. The enzymatic method shows the highest protein extraction rate at 69.91% with a mean protein content of 60.19 g/100 g, while extraction with NaOH or ascorbic acid resulted in rates of 60.44 and 46.34%, respectively. Further studies on technological food processing functionality and sensorial evaluation of products developed with this protein extract are recommended.